Deepening Not Departure: Xi Jinping's Governance of China's State-owned Economy. (23rd November 2021) - Leutert, Wendy; Eaton, Sarah
Abstract: To what extent has governance of China's state-owned economy changed under Xi Jinping? Against the background of momentous shifts in the political arena since 2012, some observe a decisive departure in Xi's approach to managing state-owned enterprises (SOEs): towards tight centralized control by the Chinese Communist Party and away from gradual marketization. Analysing the main aims and methods of SOE governance over the last two decades, we find that SOE policy under Xi exhibits a deepening of pre-existing trends rather than a departure. First, the essential vision of SOE functions articulated under Xi is strikingly consistent with that of his predecessors. Second, his administration's approach to governing SOEs is not novel; it relies on established mechanisms of bureaucratic design, the cadre management system, Party organizations and campaigns. While Xi has amplified Party-centred tools of command and control, this appears to be an incremental rather than a radical shift in approach.